Differential ex vivo drug resistance profile in first and subsequent relapsed childhood acute myeloid leukemia in comparison to initial diagnosis - Kuryło-Rafińska, Beata; Kołodziej, Beata; Kubicka, Małgorzata; Wysocki, Mariusz; Styczyński, Jan (Medical and Biological Sciences, 2012)
Background. Current cure rate reach 50-60% of long-term survival in childhood acute myeloblastic leukemia (AML). In spite of continuous progress in therapy of AML, relapses still occur frequently in both children and adolescents. The aim of this study was the analysis of the exvivo drug resistance profile first and subsequent relapse in childhood AML in comparison to newly diagnosed AML. Methods. The results of 76 pediatric AML samples tested for drug resistance by the MTT assay were analyzed. Up to 22 drugs were tested for each patient. Results. No significant differences between ex vivo drug resistance at first and subsequent relapse of childhood AML were found, and no drug was found for which significantly higher resistance of myeloblasts was observed at subsequent relapse, when compared to first relapse of AML. For most tested drugs, relapsed patients had higher exvivo drug resistance profile than de novo AML patients. The median RR (relative resistance between relapsed and de novo diagnosed patients) value of all 22 drugs tested was 1.6. For five drugs, RR was significantly higher at relapse: idarubicin (1.8-fold), etoposide (5.9-fold), cytarabine (1.7-fold), fludarabine (3.7-fold) and busulfan (4.3-fold). For other four drugs, a trend for higher resistance at relapse was observed: for daunorubicin, mitoxantrone, L-asparaginase and cladribine. Conclusion. Ex vivo drug resistance profile in relapsed childhood AML is higher in comparison to initial diagnosis, however we did not find differences in ex vivo drug resistance between first and subsequent relapse of AML.